Representations of Children in Street Situation in Brazilian Literature from the 16th to the 20th Century: Journeys of a (De)constructed Field - Brazil, Priscila Nunes; Batista, Maria Thais de Oliveira; Araújo, Francisco Roberto Diniz (Revista Letras Raras, 2023)
The present article aims to analyze the representation of children in conditions of social vulnerability in Brazilian literature, focusing on characters facing marginalization and homelessness. We conducted a bibliographical research that discusses childhood from various perspectives, tracing a historical overview of children in situations of need and homelessness, as depicted by renowned authors selected to compose the research corpus. Brazilian literature has consistently engaged with social issues of each era, as evident in works such as A Escrava Isaura by Bernardo Guimarães, Memórias Póstumas de Brás Cubas by Machado de Assis, O Cortiço by Aluísio de Azevedo, Capitães da Areia by Jorge Amado, and Grande Sertão Veredas by Guimarães Rosa. The analyzed works portray the so-called "excluded" individuals from society, marginalized and often deprived of documentation or a home, practically considered non-existent. In this regard, the present study draws theoretical support from authors like Machado (2006), Kramer (2003), Polinésio (1994), and the Statute of the Child and Adolescent (1990) document. Consequently, Brazilian children living on the streets, long disregarded for centuries, have now drawn the attention of society, which can no longer afford to ignore this issue.